Accretion of a clumped wind from a red supergiant donor on to a magnetar is suggested by the analysis of the XMM–Newton and NuSTAR observations of the X-ray binary 3A 1954+319. Issue 3 (20th December 2021) - Bozzo, E; Ferrigno, C; Oskinova, L; Ducci, L
ABSTRACT: 3A 1954+319 has been classified for a long time as a symbiotic X-ray binary, hosting a slowly rotating neutron star and an aged M red giant. Recently, this classification has been revised thanks to the discovery that the donor star is an M supergiant. This makes 3A 1954+319 a rare type of high-mass X-ray binary consisting of a neutron star and a red supergiant donor. In this paper, we analyse two archival and still unpublished XMM–Newton and NuSTAR observations of the source. We perform a detailed hardness ratio-resolved spectral analysis to search for spectral variability that could help investigating the structures of the inhomogeneous M supergiant wind from which the neutron star is accreting. We discuss our results in the context of wind-fed supergiant X-ray binaries and show that the newest findings on 3A 1954+319 reinforce the hypothesis that the neutron star in this system is endowed with a magnetar-like magnetic field strength (≳ 10 14  G).